Prediction Method for Overconsolidation Ratio of Marine SoftSoil Based on the Piezocone Penetration Tests. (30th July 2019) - Fu, Yanbin; Zhang, Sizhan; Lv, Guiyang; Han, Kaihang
Abstract : Because of the strong structural and sensitive behavior, the properties of marine soft soil change greatly when subjected to external disturbances, which leads to great difficulty in reflecting its real mechanical properties in the laboratory soil tests. The piezocone penetration test (CPTU) is one of the main technologies for in situ testing of geotechnical engineering. CPTU has the advantages of being fast and convenient, no sampling, low disturbance to soil, large amount of data, and reliable testing. The determination of the overconsolidation ratio (OCR) based on the CPTU results can solve the problems of soil disturbance and stress release, which occur during the consolidation test in the laboratory. However, there are still some problems such as lack of strict theoretical analysis of penetration mechanism and incomplete interpretation theory of in situ test parameters of CPTU. In this paper, the CPTU cone head is assumed to be hemispherical considering the penetration mechanism of CPTU. Moreover, the compaction modes of the CPTU probe penetrating into soil are adopted as spherical and cylindrical cavity expansion modes, respectively. The ultimate expansion pressures of the probe penetrating into soil under the spherical and cylindrical cavity expansion modes are first obtained by virtue of the theory of cavity expansion. Then, two prediction methods for OCR considering the roughness and penetration rate of the cone are proposed by combining the ultimate expansion pressures of the probe penetrating the approximate closed solution of cavity expansion in the modified Cambridge model, which is suitable for predicting the OCR of marine soft clay. Finally, to verify the reliability of the two proposed prediction methods, comparisons with the in situ CPTU tests of marine soft clay in two coastal areas and two existing prediction methods are made. The comparison results show that predictions of OCR of marine soft clay in this paper are close to Wayne's method and more accurate than Chanmee's method since the factors such as cone roughness and penetration rate are considered in the new proposed prediction methods. In order to improve the applicability in different cases of the OCR predictions, the average values of the two proposed methods are recommended as the reference value for the OCR of marine soft soil.